Kegiatan Penanaman Kembali Bibit Mangrove untuk Pelestarian Buah Bakau sebagai Bahan Pembuatan Sirup di Desa Wonorejo Surabaya - Anggraeni Luthfiyatul Afifah; As Dewi Aman Meker; Wedar Putri Sholehati; Nur Elsa Choiru Ummah; Muhammad Yusron Maulana El–Yunusi (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
An important effort to preserve the ecosystem is the replanting of mangrove seedlings in Wonorejo Village, Surabaya. This activity not only focuses on environmental preservation but also seeks to increase economic potential through processing mangrove products, such as mangrove syrup. The purpose of this activity is to increase public awareness of the importance of protecting the environment and the use of mangrove fruit as a basic ingredient for making syrup, which is very nutritious and economically beneficial. The method used is the Asset-Based Community Development (ABCD) approach. This method includes location selection, selection of mangrove types, socialization, and community involvement and training during the planting and processing process. The results of the activity show that the community is more aware of the importance of preserving the environment and improving the local economy through the use of mangrove syrup products, which helps the sustainability of the mangrove ecosystem and progress in local products.